A Quantitative Study on the Effects of Perceived Enjoyment and Mobility on Perceived Ease of Use and User Satisfaction - Febyscilla Swagesti DSE; Rahmad Solling Hamid; H. Hafid (Manunggal Halim Jaya, 2026)
This study examines how perceived enjoyment and mobility influence perceived ease of use and user satisfaction with Bank Sulselbar's mobile banking application. Specifically, this research addresses two questions: (1) Do perceived enjoyment and mobility significantly affect perceived ease of use? and (2) Do these factors directly or indirectly influence user satisfaction through perceived ease of use? To answer these questions, a quantitative explanatory research design based on an extended Technology Acceptance Model (TAM) was employed. Data were collected from 200 active users of Bank Sulselbar mobile banking through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.3.1. The results show that mobility has a strong positive effect on perceived ease of use and indirectly enhances user satisfaction through full mediation by perceived ease of use. In contrast, perceived enjoyment has a negative and significant effect on perceived ease of use and indirectly reduces user satisfaction. Moreover, perceived ease of use emerges as the most dominant determinant of user satisfaction, accounting for 70.1% of the variance. These findings indicate that functional accessibility plays a more critical role than hedonic experience in shaping user satisfaction in regional mobile banking services. From a practical perspective, this study provides important implications for banking practitioners, particularly regional banks. Improving system usability, simplifying navigation, and ensuring stable access across different usage conditions are more effective strategies for enhancing user satisfaction than emphasizing visual or entertainment features. Prioritizing ease of use can strengthen customer satisfaction, encourage continued use, and support financial inclusion by providing accessible digital banking services.